PEMANFAATAN WORDWALL SEBAGAI MEDIA PEMBELAJARAN: PELATIHAN GURU DI SMA MUHAMMADIYAH 1 TAMAN SIDOARJO - Suhartono Suhartono; Bernadetta Budi Lestari; Pandu Rudi Widyatama; Agnes Sandri Diana Selek; Kinanda Pandu Listanto (LPPM Universitas Bina Bangsa, 2022)
Academics including lecturers, students, and educators are expected to contribute integrally to the implementation of the Tri dharma in higher education. As we understand education is a means for the state to produce superior human resources. The creation of a quality educational academic atmosphere is inseparable from supporting factors, in addition to curriculum design and learning infrastructure prepared in such a way, no less important is the role of a teacher in the implementation of teaching and learning activities in their respective classes. In the field, in the practice of teaching and learning activities, there are still many teachers who have not utilized and maximized the availability of technological developments and digital platforms that are already available in teaching and learning practices. Academics including lecturers, students, and educators are expected to contribute integrally to the implementation of the Tri dharma in higher education. As we understand education is a means for the state to produce superior human resources. The creation of a quality educational academic atmosphere is inseparable from supporting factors, in addition to curriculum design and learning infrastructure prepared in such a way, no less important is the role of a teacher in the implementation of teaching and learning activities in their respective classes. In the field, in the practice of teaching and learning activities, there are still many teachers who have not utilized and maximized the availability of technological developments and digital platforms that are already available in teaching and learning practices. So it is felt that there is a need for concrete efforts in providing skills training for teachers as educators in schools in order to increase their competence in utilizing digital platforms as a suggestion for learning media through community service activities. The availability of digital platforms is expected to help make it easier for teachers to support teaching and learning activities in schools, so that learning objectives can be achieved optimally. Talking about many kinds of digital platforms through the internet, on this occasion the team of lecturers of the PPKn study program, Faculty of Social Sciences and Humanities, PGRI Adi buana University Surabaya in collaboration with SMA Muhammadiyah 1 Taman Sidoarjo regency will carry out community service activities. In this activity, training activities were carried out on teachers of Muhammadiyah 1 Taman High School in utilizing digital platforms, especially the use of the Worldwall application as a means of learning media. The Worldwall application can be used and managed by teachers to become a fun and not boring learning medium for students. Training and mentoring for teachers in the use of the Worldwall platform as a learning medium was chosen to produce an interesting learning atmosphere based on audio, visual and digital, so that learning is preferred and not boring for students. With this activity, teachers at SMA Muhammadiyah 1 Taman Sidoarjo have new skills and competencies in utilizing technology, especially the use of the Worldwall platform, so that later it can be used as a medium in teaching and learning activities carried out